In-situ manganese-loaded ferric-aluminum-humic acid floc biochar material, preparation method and application thereof

CN118681581BActive Publication Date: 2026-10-23ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410594003.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-14
Publication Date
2026-10-23
Estimated Expiration
2044-05-14

AI Technical Summary

Technical Problem

目前,作为通用混凝剂的铝盐和铁盐混凝剂净化腐殖酸地表水的研究受到广泛关注,然而混凝后的金属残留及高出水浊度会对水体环境带来进一步的危害,因此如何将混凝去除腐殖酸地表水工艺产生的絮体污泥进行合理的处理处置已成为当今不可避免的环境问题

Benefits of technology

[0020]本发明提供了一种原位载锰铁铝腐殖酸絮体生物炭材料的制备方法,包括以下步骤:将含腐殖酸水中依次加入高锰酸钾和聚合铝铁/阳离子聚丙烯酰胺共价键型絮凝剂混合,进行氧化混凝沉淀反应,得到含腐殖酸絮体;将含腐殖酸絮体在氮气下进行热解,得到原位载锰铁铝腐殖酸絮体生物炭材料。本发明利用高锰酸钾预氧化-聚合铝铁/阳离子聚丙烯酰胺共价键型絮凝剂混凝工艺处理含腐殖酸水,不仅在低投加量,低金属残留下可以有效去除腐殖酸,而且通过氧化混凝沉淀反应收集生成的腐殖酸絮体,制备原位载锰铁铝生物炭,该方法制备生物炭中的锰铝铁氮等元素来自于高锰酸钾氧化剂、聚合铝铁/阳离子聚丙烯酰胺共价键型絮凝剂、天然的腐殖酸,不需要在生物炭制备中外加锰铝铁氮元素,实现了氧化混凝絮体废弃物的资源化利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118681581B_ABST
    Figure CN118681581B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of wastewater treatment, and particularly relates to in-situ manganese-iron-aluminum-humic acid floc loaded biochar material and a preparation method and application thereof. The present application uses potassium permanganate pre-oxidation-polyaluminum iron / cationic polyacrylamide covalent bond type flocculant coagulation process to treat humic acid-containing water, which can effectively remove humic acid under the conditions of low dosage and low metal residue, and can collect the generated humic acid floc through oxidation coagulation sedimentation reaction to prepare in-situ manganese-iron-aluminum biochar. The manganese, aluminum, iron and nitrogen elements in the biochar prepared by the method come from the potassium permanganate oxidant, the polyaluminum iron / cationic polyacrylamide covalent bond type flocculant and the natural humic acid, and there is no need to add manganese, aluminum, iron and nitrogen elements in the preparation of biochar, so that the resource utilization of oxidation coagulation floc waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to an in-situ supported manganese-iron-aluminum humic acid flocculent biochar material, its preparation method, and its application. Background Technology

[0002] Humic acid, as one of the main components of natural organic matter, is widely present in surface water. Coagulation is one of the most commonly used processes for removing humic acid due to its low cost, simple operation, and good effect. Currently, research on the purification of humic acid-laden surface water using aluminum and iron salt coagulants, which are general-purpose coagulants, has received widespread attention. However, the metal residues and high effluent turbidity after coagulation can further harm the aquatic environment. Therefore, how to properly treat and dispose of the flocculent sludge generated from the coagulation process for removing humic acid from surface water has become an unavoidable environmental problem. Chinese patent CN201510937936.1 discloses a method for degrading humic acid in water by electro-co-activating persulfate with ferrous sulfate. This method activates persulfate with ferrous sulfate to generate sulfate free radicals, which can degrade most humic acid-like organic pollutants. It can be applied to groundwater, drinking water plants, and industrial wastewater. This method has the advantages of simple operation, low cost, and non-toxicity, but it also consumes a lot of electricity. Furthermore, the electro-co-activation of persulfate with ferrous sulfate has different degradation effects on different types of humic acid, limiting its applicability.

[0003] In recent years, converting waste flocculent sludge into biochar-based adsorbents or catalysts via pyrolysis has been considered a viable option for sludge treatment due to its ability to significantly reduce sludge volume and produce high-value-added carbon materials for further applications. The carbonization of waste flocculent sludge, while generating flocculent biochar, can eliminate toxic organic pollution and immobilize heavy metals, reducing environmental toxicity. Chinese patent CN202210679720.X discloses a flocculent-based magnetic biochar, its preparation method, and its applications, which boasts advantages such as low cost and high application potential. It can achieve the recycling of potential pollutants and reduce secondary environmental pollution; however, the preparation process is complex and its scalability is limited. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention provides an in-situ supported manganese, iron, and aluminum humic acid flocculant biochar material, its preparation method, and its application. The preparation method of this invention utilizes manganese, aluminum, iron, and nitrogen elements in the prepared biochar from potassium permanganate oxidant, polyaluminum iron / cationic polyacrylamide covalently bonded flocculant, and natural humic acid. This eliminates the need for external addition of manganese, aluminum, iron, and nitrogen elements during biochar preparation, enabling the resource utilization of oxidized coagulated flocculant waste.

[0005] To achieve the above objectives, the present invention provides the following technical solutions.

[0006] This invention provides a method for preparing in-situ supported manganese-iron-aluminum humic acid flocculent biochar material, comprising the following steps:

[0007] Potassium permanganate and polyaluminum iron / cationic polyacrylamide covalent flocculant were added sequentially to water containing humic acid and mixed to carry out an oxidative coagulation and precipitation reaction to obtain humic acid-containing flocs.

[0008] The humic acid-containing flocs were pyrolyzed under nitrogen to obtain in-situ manganese-iron-aluminum humic acid-supported flocs biochar material.

[0009] Preferably, the amount of potassium permanganate used is 0.2 mg / L to 1.2 mg / L, based on 1 L of humic acid-containing water.

[0010] Preferably, the concentration of humic acid in the humic acid-containing water is 10 mg / L to 100 mg / L;

[0011] Based on 1L of humic acid-containing water, the dosage of the polyaluminum iron / cationic polyacrylamide covalent flocculant is 10mg to 60mg.

[0012] Preferably, the process before pyrolysis further includes drying and pulverizing the humic acid-containing flocs sequentially, wherein the drying temperature is 60–80°C and the drying time is 12–24 hours.

[0013] Preferably, the pyrolysis temperature is 600–800℃, and the pyrolysis time is 1–2 h; during the pyrolysis, the flow rate of nitrogen gas is 50–100 mL / min.

[0014] Preferably, the pyrolysis process further includes sequentially washing the pyrolysis product with water, centrifuging, and drying the resulting solid phase.

[0015] The present invention also provides an in-situ manganese-iron-aluminum humic acid flocculent biochar material prepared by the above-described preparation method, characterized in that it includes humic acid biochar and alumina, iron oxide, manganese oxide and nitrogen-containing compounds loaded on the surface and internal pores of humic acid biochar.

[0016] Preferably, the mass ratio of the biochar, aluminum in alumina, iron in iron oxide, manganese in manganese oxide, and nitrogen in the nitrogen-containing compound is 8.5–40:4.4–20:2.2–10:0.16–1.

[0017] This invention also provides the application of the in-situ manganese-iron-aluminum humic acid-loaded flocculent biochar material prepared by the aforementioned preparation method, or the application of the aforementioned in-situ manganese-iron-aluminum humic acid-loaded flocculent biochar material in the treatment of tetracycline-containing wastewater.

[0018] This invention also provides a method for treating tetracycline-containing wastewater, comprising the following steps:

[0019] In-situ manganese-iron-aluminum humic acid flocculent biochar material and peroxymonosulfate were added to tetracycline wastewater, and the pH was adjusted to 3-11 for wastewater treatment.

[0020] This invention provides a method for preparing in-situ manganese-iron-aluminum humic acid-supported flocculant biochar material, comprising the following steps: potassium permanganate and polyaluminum-iron / cationic polyacrylamide covalently bonded flocculant are sequentially added to humic acid-containing water and mixed to carry out an oxidative coagulation and precipitation reaction to obtain humic acid-containing flocs; the humic acid-containing flocs are then pyrolyzed under nitrogen to obtain in-situ manganese-iron-aluminum humic acid-supported flocculant biochar material. This invention utilizes a potassium permanganate pre-oxidation-polyaluminum-iron / cationic polyacrylamide covalently bonded flocculant coagulation process to treat humic acid-containing water. This process effectively removes humic acid with low dosage and low metal residue. Furthermore, the humic acid flocs generated through the oxidative coagulation and precipitation reaction are collected to prepare in-situ manganese-iron-aluminum-supported biochar. The manganese, aluminum, iron, and nitrogen elements in the biochar prepared by this method originate from the potassium permanganate oxidant, the polyaluminum-iron / cationic polyacrylamide covalently bonded flocculant, and the natural humic acid, eliminating the need for external addition of manganese, aluminum, iron, and nitrogen elements during biochar preparation and achieving resource utilization of oxidative coagulation flocculant waste. Attached Figure Description

[0021] Figure 1 The chemical structure diagrams of the biochar samples (b), (c), (d), and (e) were analyzed using Raman spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and hysteresis loop analysis, respectively.

[0022] Figure 2 The diagram shows the effects of different systems on the treatment of tetracycline wastewater. Detailed Implementation

[0023] This invention provides a method for preparing in-situ manganese-iron-aluminum humic acid flocculent biochar material, comprising the following steps:

[0024] Potassium permanganate and polyaluminum iron / cationic polyacrylamide covalent flocculant were added sequentially to water containing humic acid and mixed to carry out an oxidative coagulation and precipitation reaction to obtain humic acid-containing flocs.

[0025] The humic acid-containing flocs were pyrolyzed under nitrogen to obtain in-situ manganese-iron-aluminum humic acid-supported flocs biochar material.

[0026] This invention involves sequentially adding potassium permanganate and polyaluminum iron / cationic polyacrylamide covalent flocculant to humic acid-containing water, mixing them together, and carrying out an oxidative coagulation and precipitation reaction to obtain humic acid-containing flocs.

[0027] In this invention, the preparation of the polyaluminum iron / cationic polyacrylamide covalent flocculant is carried out in accordance with CN113136004A.

[0028] In this invention, the concentration of humic acid in the humic acid-containing water is preferably 10 mg / L to 100 mg / L, more preferably 10 mg / L to 60 mg / L.

[0029] In this invention, the amount of potassium permanganate used is 0.2 mg to 1.2 mg per 1 L of humic acid-containing water, more preferably 0.5 mg to 1 mg.

[0030] In this invention, the amount of the polyaluminum iron / cationic polyacrylamide covalent flocculant is preferably 10mg to 60mg, more preferably 20mg to 60mg, based on 1L of humic acid-containing water.

[0031] After obtaining humic acid-containing flocs, the present invention pyrolyzes the humic acid-containing flocs under nitrogen to obtain in-situ manganese-iron-aluminum humic acid-containing floc biochar material.

[0032] In this invention, the process before pyrolysis includes drying and pulverizing the humic acid-containing flocs in sequence;

[0033] In this invention, the drying temperature is preferably 60-80°C, more preferably 70°C; the drying time is preferably 12-24 hours, more preferably 15-20 hours.

[0034] In this invention, during the pyrolysis, the flow rate of nitrogen gas introduced is preferably 50 mL / min to 100 mL / min, more preferably 60 mL / min to 80 mL / min.

[0035] In this invention, the pyrolysis temperature is preferably 600–800°C, more preferably 700°C, and the pyrolysis time is preferably 1–2 h, more preferably 1.5 h. In this invention, the heating rate to the pyrolysis temperature is preferably 5–10°C / min, more preferably 10°C / min.

[0036] The present invention also provides an in-situ manganese-iron-aluminum humic acid flocculent biochar material prepared by the above preparation method, comprising humic acid biochar and alumina, iron oxide, manganese oxide and nitrogen-containing compounds loaded on the surface and internal pores of humic acid biochar.

[0037] In this invention, the nitrogen-containing compound preferably includes pyridine nitrogen and graphitic nitrogen.

[0038] In this invention, the mass ratio of the biochar, aluminum in alumina, iron in iron oxide, manganese in manganese oxide, and nitrogen in the nitrogen-containing compound is (8.5-40):(4.4-20):(2.2-10):(0.16-1), more preferably 40:20:10:1.

[0039] This invention also provides the application of the in-situ manganese-iron-aluminum humic acid flocculent biochar material prepared by the above preparation method in the treatment of tetracycline-containing wastewater.

[0040] This invention also provides a method for treating tetracycline-containing wastewater, comprising the following steps:

[0041] In-situ manganese-iron-aluminum humic acid flocculent biochar material and peroxymonosulfate were added to tetracycline wastewater, and the pH was adjusted to 3-11 for wastewater treatment.

[0042] In this invention, during wastewater treatment, based on 1L of tetracycline wastewater, the preferred dosage of the in-situ supported manganese-iron-aluminum humic acid flocculent biochar material is 0.05g to 1.0g; the preferred dosage of the peroxymonosulfate is 0.03mmol to 0.1mmol.

[0043] In this invention, the concentration of tetracycline in the tetracycline wastewater is preferably 5 mg / L to 50 mg / L, more preferably 10 mg / L to 40 mg / L.

[0044] In this invention, the pH-adjusting reagent is preferably hydrochloric acid or sodium hydroxide.

[0045] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1

[0047] Preparation of in-situ loaded manganese-iron-aluminum humic acid flocculent biochar material (MAFBC-800):

[0048] (1) Add 0.8 mg of potassium permanganate to 1 L of humic acid water, oxidize at 300 r / min for 5 min, and then mix with 25 mg of polyaluminum iron / cationic polyacrylamide covalent flocculant. Under the coagulation hydraulic conditions of fast stirring speed 350 r / min, fast stirring time 5 min, slow stirring speed 50 r / min, slow stirring time 30 min, and settling time 30 min, collect the flocs.

[0049] (2) The collected flocs were dried at 80°C for 24 hours and then ground into powder by a pulverizer and passed through an 80-mesh sieve. The resulting flocs were then ready for use.

[0050] (3) The above flocs were pyrolyzed in a tubular furnace at a N2 flow rate of 100 mL / min and a heating rate of 10 °C / min to 800 °C, with a residence time of 1 h. The resulting product was collected and washed three times with deionized water until the pH was close to neutral. The product was then dried in an oven at 70 °C to obtain in-situ manganese-iron-aluminum humic acid floc biochar material (humic acid floc biochar loaded with alumina, iron oxide, manganese oxide and nitrogen-containing compounds, including pyridine nitrogen and graphitic nitrogen), namely MAFBC-800.

[0051] In Example 1, the mass ratio of humic acid flocculent biochar, aluminum in alumina, iron in iron oxide, manganese in manganese oxide, and nitrogen in nitrogen-containing compounds is 40:20:10:1.

[0052] Example 2

[0053] The only difference from Example 1 is that the pyrolysis temperature in step (3) is replaced with 700°C, and the product generated is denoted as MAFBC-700.

[0054] Example 3

[0055] The only difference from Example 1 is that the pyrolysis temperature in step (3) is replaced with 500°C, and the resulting product is denoted as MAFBC-500.

[0056] Comparative Example 1

[0057] The humic acid drug powder was pyrolyzed in a tube furnace at a N2 flow rate of 100 mL / min and a heating rate of 10 °C / min to 800 °C, and held at that temperature for 1 h. The resulting product was collected and washed three times with deionized water until the pH was close to neutral. The product was then dried in an oven at 70 °C to obtain humic acid powder biochar (HBC-800).

[0058] Comparative Example 2

[0059] Preparation of in-situ iron-aluminum biochar (AFBC-800) for coagulation and humic acid removal flocs:

[0060] (1) 1L of humic acid-containing water was treated with 25mg of polyaluminum iron / cationic polyacrylamide covalent flocculant. The coagulation hydraulic conditions were: fast stirring speed 350r / min, fast stirring time 5min, slow stirring speed 50r / min, slow stirring time 30min, and settling time 30min. The flocs were then collected.

[0061] (2) The obtained flocs were dried at 80°C for 24 hours and then ground into powder by a pulverizer and passed through an 80-mesh sieve. The flocs were then ready for use.

[0062] (3) The above flocs were pyrolyzed in a tubular furnace at a N2 flow rate of 100 mL / min and a heating rate of 10 °C / min to 800 °C, with a residence time of 1 h. The resulting product was collected and washed three times with deionized water until the pH was close to neutral. The product was then dried in an oven at 70 °C to obtain in-situ iron-aluminum biochar material (AFBC-800).

[0063] Figure 1 (b) shows the Raman spectra of HBC-800, AFBC-800, MAFBC-800, MAFBC-700, and biochar samples. Figure 1 (b) It can be seen that the spectra of HBC, AFBC, and MAFBC are at 1354 cm⁻¹. -1 and 1592cm -1 There are two main bands, which belong to disordered sp. 2 Hybrid carbon (d-band) and crystalline graphite structures in porous carbon (g-band). Among them, compared to MAFBC-700, when the pyrolysis temperature is increased to 800℃, the Ig of different biochar samples... D / I G The increase is due to the higher pyrolysis temperature, leading to further collapse and reshaping of the carbon matrix. Higher pyrolysis temperatures promote the growth of edge defect structures in the carbon framework and the recovery of aromatic structures. Furthermore, AFBC and MAFBC exhibit higher Ig content. D / I G The high value may be due to carbon layer distortion caused by Fe, Mn, and O doping. Typically, a large number of unpaired electrons reside at defective edge structures in the carbon network, enhancing electron penetration and transfer at the carbon surface. Therefore, defect sites generated in AFBCs and MAFBCs are beneficial for improving their catalytic performance.

[0064] Figure 1 (c) Fourier transform infrared spectra of HBC-800, AFBC-800, MAFBC-800, MAFBC-700, and MAFBC-500 biochar samples. Figure 1 (c) It can be seen that, among all samples, the 1060cm... -1 1625cm -1 and 3430cm -1 The peaks centered at 875 cm⁻¹ correspond to the stretching and bending vibrations of the CO group, C=C / C=O group, and -OH group, respectively. For HBC, the peaks are approximately at 875 cm⁻¹. -1 and 1459cm -1 The peak at 570 cm⁻¹ represents the bending and stretching vibrations of the CH bonds in aromatic hydrogens. For AFBC and MAFBC, the peak at 570 cm⁻¹ represents the bending and stretching vibrations of the CH bonds. -1 and 482cm -1The new peak at this location is attributed to the bending vibrations of Mn-O and Al-O bonds. This confirms the presence of oxygen-containing functional groups and metal oxides in the flocculent biochar composite material.

[0065] Figure 1 (d) X-ray diffraction analysis of the crystal structures of HBC-800, AFBC-800, MAFBC-800, and MAFBC-700 biochar samples. In all samples, the broad diffraction peak at approximately 26° was considered to be a surface of the graphitic carbon crystal. The high-intensity and sharp diffraction peaks in HBC-800 within the 30°–50° range belonged to other metallic crystal impurities such as Na and Mg, which were doped with the humic acid powder. AFBC and MAFBC produced more aluminum, iron, and manganese oxides, such as Al₂O₃ (2θ = 44.1°), Fe₂O₃ (2θ = 36.6°), and Mn₃O₄ (2θ = 44.12°). Compared to MAFBC-700, the biochar samples (HBC, AFBC, MAFBC) with a pyrolysis temperature of 800℃ showed increased intensity of characteristic peaks, indicating that the increased pyrolysis temperature led to carbon layer deformation and increased carbon surface defects. Therefore, the spectra show that AFBC-800 and MAFBC-800 produced more defects than MAFBC-700, which is beneficial to enhancing the electron transfer performance of the catalyst.

[0066] Figure 1 (e) The magnetic properties of AFBC-800 and MAFBC-800 were tested by hysteresis curves. The saturation magnetization values ​​of AFBC-800 and MAFBC-800 were 3.286 emu / g and 3.985 emu / g, respectively, which can be rapidly adsorbed onto external magnets, indicating that the prepared catalysts have excellent separation and recovery capabilities.

[0067] Test case

[0068] The prepared polyaluminum iron / cationic polyacrylamide covalent flocculant was applied at different concentrations to a humic acid-containing substance to investigate its humic acid removal effect. The results are shown in Table 1.

[0069] Table 1. Effect of polyaluminum ferric / cationic polyacrylamide covalent flocculant on humic acid treatment.

[0070]

[0071]

[0072] The results in Table 1 show that the polyaluminum iron / cationic polyacrylamide covalent flocculant removed 91.3% of humic acid at a dosage of 25 mg / L, indicating that the polyaluminum iron / cationic polyacrylamide covalent flocculant has a good removal effect on humic acid.

[0073] (2) When the dosage of polyaluminum iron / cationic polyacrylamide covalent flocculant is 25 mg / L, different dosages of potassium permanganate oxidant are applied to humic acid to investigate its effect on removing humic acid. The results are shown in Table 2.

[0074] Table 2. Effects of potassium permanganate pre-oxidation-polyaluminum ferric / cationic polyacrylamide covalent flocculant coagulation process on humic acid treatment.

[0075]

[0076]

[0077] The results in Table 2 show that potassium permanganate pre-oxidation combined with polyaluminum iron / cationic polyacrylamide covalent flocculant coagulation can achieve efficient and stable organic matter removal at a low dosage.

[0078] (3) The specific surface area and particle size of the flocs formed after coagulation with polyaluminum iron / cationic polyacrylamide covalent flocculant and the flocs formed by potassium permanganate pre-oxidation-polyaluminum iron / cationic polyacrylamide covalent flocculant coagulation process were compared and the results are shown in Table 3.

[0079] Table 3. Specific surface area and particle size of flocs formed after coagulation with polyaluminum ferrophosphate / cationic polyacrylamide covalent flocculant and flocs formed after coagulation with potassium permanganate pre-oxidation-polyaluminum ferrophosphate / cationic polyacrylamide covalent flocculant.

[0080]

[0081] Application Example 1

[0082] (1) Add 0.4 g / L of biochar material obtained in the example or comparative example and 0.05 mM peroxymonosulfate (PMS) to 100 mL of 10 mg / L tetracycline wastewater, or add 100 mL of 10 mg / L tetracycline wastewater at the same time, and place the system in a constant temperature shaker at 25°C and 150 rpm for 60 min.

[0083] (2) At predetermined time intervals, a certain volume of supernatant was extracted using a syringe. The concentration of residual tetracycline was determined by measuring the absorbance of the supernatant after membrane treatment at 359 nm using a UV-Vis spectrophotometer. The results are shown in Table 4 and Figure 2 .

[0084] Table 4. Effects of different materials on tetracycline wastewater treatment

[0085]

[0086]

[0087] The results showed that the adsorption and degradation performance of AFBC-800 and MAFBC-800 alone for tetracycline was limited. The degradation of tetracycline by a single peroxymonosulfate system was also generally poor. Due to the presence of various iron and manganese, the activation of peroxymonosulfate was accelerated. The AFBC-800 / PMS and MAFBC-800 / PMS systems removed 63.2% and 65.8% of tetracycline, respectively, within 1 minute, which significantly improved the removal rate of tetracycline.

[0088] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing in-situ manganese-iron-aluminum humic acid flocculent biochar material, characterized in that, Includes the following steps: Potassium permanganate and polyaluminum iron / cationic polyacrylamide covalent flocculant were added sequentially to humic acid-containing water and mixed to carry out oxidative coagulation and precipitation reaction to obtain humic acid-containing flocs; the humic acid-containing flocs were pyrolyzed under nitrogen to obtain in-situ manganese iron aluminum humic acid floc biochar material. The in-situ loaded manganese-iron-aluminum humic acid flocculent biochar material includes humic acid biochar and aluminum oxide, iron oxide, manganese oxide and nitrogen-containing compounds loaded on the surface and internal pores of humic acid biochar. Based on 1L of humic acid-containing water, the amount of potassium permanganate used is 0.2mg~1.2mg; The concentration of humic acid in the humic acid-containing water is 10 mg / L to 100 mg / L; The pyrolysis temperature is 600~800℃, and the pyrolysis time is 1~2h; Based on 1L of humic acid-containing water, the dosage of the polyaluminum iron / cationic polyacrylamide covalent flocculant is 10mg~60mg.

2. The preparation method according to claim 1, characterized in that, Before pyrolysis, the humic acid-containing flocs are successively dried and pulverized. The drying temperature is 60-80℃ and the drying time is 12-24h.

3. The preparation method according to claim 1, characterized in that, During the pyrolysis, the flow rate of nitrogen gas introduced is 50~100 mL / min.

4. The preparation method according to claim 1, characterized in that, The process after pyrolysis also includes washing the pyrolysis product with water, centrifuging it, and drying the resulting solid phase.

5. The in-situ manganese-iron-aluminum humic acid flocculent biochar material prepared by the preparation method according to any one of claims 1 to 4, characterized in that, It includes humic biochar and alumina, iron oxide, manganese oxide and nitrogen-containing compounds loaded on the surface and internal pores of humic biochar.

6. The application of the in-situ manganese-iron-aluminum humic acid flocculent biochar material as described in claim 5 in the treatment of tetracycline-containing wastewater.

7. A method for treating tetracycline-containing wastewater, characterized in that, Includes the following steps: The in-situ supported manganese-iron-aluminum humic acid flocculent biochar material as described in claim 5 and peroxymonosulfate were added to tetracycline-containing wastewater, and the pH was adjusted to 3-11 for wastewater treatment.

Citation Information

Patent Citations

  • Method for degrading humic acid in water through activating persulfates by electric synergistic ferrous iron

    CN105439250A

  • Polymeric aluminum-iron / cationic polyacrylamide covalent bond type flocculant as well as preparation method and application thereof

    CN113136004A

  • Adsorption condensation method for removing natural organic matter in water by enhancing micro-interface adsorption

    CN102344180A

  • Boron-doped ferro-manganese magnetic biochar material as well as preparation method and application thereof

    CN113332995A

  • Magnetic biochar based on floc as well as preparation method and application of magnetic biochar

    CN115090316A